Nigerian Pentecostalism Observed: Theological Exploration on Miracles, Deliverance, and Prosperity Gospel - Brendan, Mujah C. (Journal of African Studies and Sustainable Development, 2022)
This article examines the phenomenon of Pentecostalism from its pristine origins to how it has come to be a global force in Christianity and Nigeria in particular. Nigeria today is home to some of the most renowned Pentecostal churches in the world, and it is exporting same to other parts of the world. Phenomenological method is applied in this exploration of the Pentecostal style of messaging and practice in the areas of miracles, deliverance, and prosperity gospel. Nigeria today is plagued by numerous economic challenges, social negligence and political myopia that has pauperize the greater percentage of the population. People therefore seek solutions to their problems in God and religion. Pentecostalism has proven handy in responding to this need. Tapping into the existing African highly spiritualized cosmology, it has spiritualized every problem and made their members dependent on God for solutions to basic human problems, nowhere is this more visible than in the phenomenon of miracles, deliverance, and the prosperity gospel.
free